Security assessment : case studies for implementing the NSA IAM - Miles, Greg.; Rogers, Russ. (Rockland : Syngress, 2004)
The National Security Agency's INFOSEC Assessment Methodology (IAM) provides guidelines for performing an analysis of how information is handled within an organization: looking at the systems that store, transfer, and process information. It also analyzes the impact to an organization if there is a loss of integrity, confidentiality, or availability. This book shows how to do a complete security assessment based on the NSA's guidelines. This book also focuses on providing a detailed organizational information technology security assessment using case studies. The Methodology used for the assessment is based on the National Security Agency's (NSA) INFOSEC Assessment Methodology (IAM). Examples will be given dealing with issues related to military organizations, medical issues, critical infrastructure (power generation etc). The book is intended to provide an educational and entertaining analysis of an organization, showing the steps of the assessment and the challenges faced during an assessment. It will also provide examples, sample templates, and sample deliverables that readers can take with them to help them be better prepared and make the methodology easier to implement. Everything You Need to Know to Conduct a Security Audit of Your Organization Step-by-Step Instructions for Implementing the National Security Agency's Guidelines Special Case Studies Provide Examples in Healthcare, Education, Infrastructure, and more.
Laying the foundation for your assessment; The pre-assessment visit; Determining the organizations information criticality -- system information criticality; The system security environment; Understanding the technical assessment plan; Customer activities; Managing the findings; Leaving no surprises; Final reporting; Tying up loose ends.
Περιέχει ευρετήριο.
Διαθέσιμο και σε ηλεκτρονικό βιβλίο, τρόπος πρόσβασης μέσω διαδικτύου.
Includes index.
Keywords: Computer security; Computers -- Access control; Information technology -- Security measures; Electronic books